Effects of the water holding bio-product lipomycin m on mesofauna groups at the melinh station for biodiversity, Vinh Phuc province - Kim Hoi, Huynh Thi; Bang Tam, Nguyen Kieu (Academia Journal of Biology, 2014)
This paper presents the study on the effects of the water holding bio-product lipomycin M on mesofauna groups at the Melinh station for Biodiversity. The results show that 25 mesofauna groups belonging to 6 classes (Chilopoda, Diplopoda, Insecta, Arachnida, Crusstacea and Oligochaeta) were recorded there. The number of the mesofauna groups are different according to the vegetation covering the soil. The average density of the mesofauna ranges between 28 and 125 individual/m2. The water holding bio-product lipomycin M has positive effects on the soil humidity, which makes advantageous condition for the mesofauna to grow and develop. Therefore, it contributes to improve the biodiversity of the soil animals.